Mild cognitive impairment: The importance of early revealing and treatment options - Stojković-Ivković Mirjana (Sestrinska reč, 2017)
Mild cognitive impairment is followed by a lot of infections, somatic disorder, cerebral and systemic diseases including AIDS. Sometimes the presence of neurologic and psychological cerebral symptoms is not affected as soul suffering and disturbance. The main characteristic of MCI is complaining on memory impairment and for get fullness, learning disabilities, low concentration tasks . It tends to be harder to learn new skills the older you become. Mild cognitive disorder refers to the clinical condition between normal aging and dementia in which persons experience memory loss to a greater extent than one would expect for age and education. It is very important to recognize mild cognitive impairment at the early stage and apply the therapy. MCI is diagnostified by anamnesis, heteroananestic data, psychology tests, neuropsychological tests, magnet resonant (MR), CT-scan, MR spectrometry, laboratory analysis and biochemical analysis of blood (KS, SE, urea, creatine, AST, ALT, hepatogram, glucose, vit B12, Fe, Waserman i Elsa test). The genetic material and CSF are rarely analysed. Etiology is not well known. Causes can be degenerative, vascular, (toxic) metabolic, traumatic in origin. A number of medications have been used to treat mild cognitive impairment. The importance of recognizing MCI and identifying it early is very useful for start treatment.